2018
DOI: 10.7759/cureus.3313
|View full text |Cite
|
Sign up to set email alerts
|

Non-ischemic Cardiomyopathy Secondary to Left Ventricular Hypertrophy due to Long-term Anabolic-androgenic Steroid Use in a Former Olympic Athlete

Abstract: Currently, the cardiovascular risk associated with the use of anabolic steroids is not well documented. Recent studies have shown that its use may potentiate the development of cardiac dysfunction in the short term. This case report describes an encounter that supports a causal link between anabolic-androgenic steroid use (AAS) and cardiomyopathy later in life. We herein present a case study of a 73-year-old prior Olympic athlete who had misused AAS for 20 years and subsequently was found to have developed a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…This raises the question of how many younger athletes are at risk. Ha et al reported a case involving an AS user who developed left ventricular hypertrophy after 20 years of AS use [19]. Pirompol et al discovered cardiomegaly in rats over an [8][9][10][11][12] week period of using AS [20].…”
Section: Cardiomyopathy and Asmentioning
confidence: 99%
“…This raises the question of how many younger athletes are at risk. Ha et al reported a case involving an AS user who developed left ventricular hypertrophy after 20 years of AS use [19]. Pirompol et al discovered cardiomegaly in rats over an [8][9][10][11][12] week period of using AS [20].…”
Section: Cardiomyopathy and Asmentioning
confidence: 99%
“…Exogenous AAS use is rapidly becoming an emergent public health concern, as some estimates indicate that 3-4 million Americans use some form of AAS [ 6 ]. AASs have been studied to show interactions within the bone, brain, endocrine, muscle, prostate, hematopoietic, and even CVD system [ 7 ]. Anabolic steroids have been linked to various cardiac adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Our case highlights an interesting presentation of a dilated cardiomyopathy with acute decompensated heart failure one year after cessation of anabolic steroids in a patient who had performed intensive physical training, and showed no improvement of the ejection fraction after cessation of the abuse and initiation of conventional heart failure therapy. In literature there are several reports documenting AAS-induced cardiotoxicity and in particular DCM [1][2][3][4][5][6][7][8][9][10][11][12][13] (Table 1) although few of them indicate irreversible effects on cardiac muscle performance [1,6,8,13] Table . We believe that what can happen in irreversible myocytes damage like in ours patient or even in fatal cases [14,15], is a more profound damage to the myocytes that can be caused by the synergism of AAS, possibly at high dosage and for a prolonged span of time with other factors that enhance the AAS damage, first of all strenuous exercise training. We will examine first the AAS general toxic effect mechanisms on cardiac myocytes and then the AAS synergism with strenous exercise and with other potential myocites damaging factors like the growth hormone (GH).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of abuse of these hormones on the body and in particular on the heart is still not entirely known. These substances can produce adverse effects on various organs, and in literature several cases of cardiac disease have been reported in athletes after previous abuse of AASs [1][2][3][4][5][6][7][8][9][10][11][12][13] documenting dilated cardiomyopathy (DCM). However only few of them have shown irreversible DCM [1,6,8,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation